A Fourth-Order Runge-Kutta Method for Numerical Solution of the Kuramoto-Sivashinsky Equation - Nizom Abdurazzokovich Taylanov; Sunatillo Хudoyor o’g’li. Urinov; Jurabek Muzaffar o’g’li Abdiev (Genius Publishing Group, 2022)
We present a numerical method for the Kuramoto-Sivashinsky equation with corresponding initial and boundary conditions. The exponential time differencing Runge-Kutta 4 method is used to solve the diagonal example of the KuramotoSivashinsky equation.
Keywords: Kuramoto–Sivashinsky equation; Integration factor; Runge-Kutta method; Exponential time differencing methods